THE PROFILE OF DENTAL CARIES IN THE FIRST YEAR STUDENTS OF ELEMENTARY SCHOOLS WITHIN THE WORKING AREA OF PUSKESMAS I DENPASAR UTARA IN 2015 - I Nyoman Gejir (Jurnal Kesehatan Gigi (Dental Health Journal), 2016)
Most frequently found oral disease in dental caries, periodontal disease, trauma and injuries and heredity lesi. School children is a group which is vulnarable todental and oral disease, especially dental caries. This study aims to know the profile of dental caries in first year student of elementary schools within working area of Puskesmas I Denpasar Utara in 2015.The research method used in this study is survey, which was conducted in 16 elementary schools within the working area of Puskesmas I Denpasar Utara with 1104 respondents (all first year students). The data was alayzed with univariate statistics to generate frequency and avarage.The finding shows that the highest occurarence of caries wasin Saraswati 2 Elementary School (45 teeth), and the lowest on was in Elementary School 20 Dangri and Dwijendra Elementary School with 9 teeth. The avarage of caries among first year students in working area of Puskesmas I Denpasar Utara was 0.3.The conclusion of this study is that the occurance of caries among first year students of Elemantary School in the working area of Puskesmas I Denpasar Utara in 2015 was relative low. Based on the conclusion above, it is suggested to refer student with dental caries to health service facilities available in the area.